DIGITAL GOVERNANCE AND WORK FROM ANYWHERE POLICY: BUREAUCRATIC REFORM STRATEGIES IN THE PUBLIC SECTOR - Richard Djiko (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2026)
Digital transformation in the public sector is driving a paradigm shift in governance towards a more adaptive, flexible, and technology-based model. One of the policies that has come to the fore is Work From Anywhere (WFA), which is seen as an innovative strategy in supporting bureaucratic reform. This study aims to analyze the relationship between digital governance and the implementation of the WFA policy as an instrument of bureaucratic reform in the public sector. This study uses a qualitative approach with literature study and policy analysis methods on various regulations, government reports, and WFA implementation practices within the framework of an electronic-based government system. The results of the study show that the success of WFA is highly dependent on the maturity of digital infrastructure, the readiness of human resources, and technology-based performance management systems. Digital governance serves as the foundation for ensuring transparency, accountability, and effectiveness of public services even though they are not physically based. In addition, WFA contributes to increased work flexibility, operational efficiency, and work-life balance for civil servants. However, challenges such as data security, performance monitoring, and organizational cultural resistance still need to be anticipated. Therefore, the integration of WFA policies into the digital governance framework is an important strategy in realizing an adaptive, responsive bureaucracy that is oriented towards quality public services.